ASPECTS OF COMMUNITARY-ACQUIRED CLOSTRIDIUM DIFFICILE INFECTION IN DOLJ COUNTY, ROMÂNIA - Livia Dragonu (Romanian Journal of Infectious Diseases, 2017)
Long regarded as a hospital-associated and antibiotic use infection, Clostridium difficile infection (CDI) has seen an increasing incidence as a community-aquired infection over the last decade. Objectives. The paper follows the particularities of CDI with a community onset, depending on the community or nosocomial origin of the infection. Material and method. Three-year retrospective study (July 1, 2014 – June 30, 2017) of 767 confirmed cases with primary CDI, hospitalized in medical units in Dolj county (România). Two groups of patients with community-onset CDI were analyzed: CA-CDI group with community origin of the infection, and NA-CDIc group with nosocomial origin. Results. CDI with community onset was identified in 453 patients (59.1% of the total); of these, 106 (23.4%) had community origin (CA-CDI) and 305 (67.3%) nosocomial (NA-CDIc). CA-CDI has increased from 4.3% (2014) to 17.9% (2017) of the total CDI, with an average of 13.1% for the study period. Compared to hospitalacquired CDI, patients with community-acquired infection were younger (median age 57 years vs 65 years), more frequently women (58.4% vs 46.2%), with lower exposure to antibiotics (75.4% vs 85.9%), lower associated immunodepression (4.7% vs 18.6%) and mortality (0.9% vs. 5.5%). Conclusions. CDI epidemiology is dynamic, the actual size of community infection requiring further assessment. CA-CDI should be considered in the investigation of community diarrhea, even in the absence of traditional risk factors (hospitalization, advanced age, antibiotic treatment.